The effect of employees satisfaction towards loyalty in hotel industry: compensation, rewards, job security and working environment / Noraslinda Mohd Said... [et al.] - Mohd Said, Noraslinda; Hamir, Norhamizan; Fadzil, Hashim; Abdul Hakim, Fairuz; Sulaiman, Suria; Mohd Yunus, Nurdayanah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Employee turnover in the hotel industry is an alarming issue. Due to the challenging job nature, employees have been jumping from one organization to another. This study aims to offer an alternative approach toward factors that lead to employee satisfaction, thus retain them with the organization. Employees satisfaction and loyalty provides significant similarities and also differences in the context of hospitality environment. This study will help the organization in providing an insight for management in the hospitality industry so that the management can re-establish their compensation and rewards program, re-evaluate the benefits given to the employees and also improving employee's work policies, to ensure a more satisfied employees and resulted in loyalty to the respective organization. Through compilation of previous literature, this study identifies the factors that affect the job satisfaction towards employees’ loyalty in hotel industry. The study outlined the factors that relate to employee’s satisfaction in hotel organization based on the compensation, rewards, job security and working environment.